PENGARUH PEMASANGAN DISTRIBUTED GENERATION TERHADAP PROFIL TEGANGAN PADA JARINGAN DISTRIBUSI - Fitrizawati, Mrs; Suharyanto, Mr; Isnaeni B.S., M (UMP, 2012)
The need for electrical energy is increasing, as more extensive network of electric power due to greater demand, as well as the distance between the centers of power to the load centers will lead to a reduction in power, because in the delivery of power from the generator to the consumer or customers there is a power loss and voltage drop. To overcome this, there is one solution that can be used to install the Distributed Generation (DG) on distribution networks. The focus of research is to see how the influence of DG before installation and after installation of DG on power distribution systems to improve voltage profile and power losses in distribution networks with variable injection and location. DG potential used is 3 pieces of micro power plants. Testing is done by simulation using ETAP Power Station 6.0 software. The simulation results show before the installation of DG voltage at the end of the network having a voltage drop of 7.06%, after the installation of DG with the injection of 85% of total capacity in section 8, the voltage drop to 1.12% successfully repaired.Key words: Distributed Generation, Voltage ProfileÂ